Respiratory and cardiac function in japanese patients with dysferlinopathy. Issue 3 (27th January 2016) - Nishikawa, Atsuko; Mori‐Yoshimura, Madoka; Segawa, Kazuhiko; Hayashi, Yukiko K.; Takahashi, Toshiaki; Saito, Yuko; Nonaka, Ikuya; Krahn, Martin; Levy, Nicolas; Shimizu, Jun; Mitsui, Jun; Kimura, En; et al.
ABSTRACT: Introduction: We retrospectively reviewed respiratory and cardiac function in patients with dysferlinopathy, including 2 autopsy cases with respiratory dysfunction. Methods: Subjects included 48 patients who underwent respiratory evaluation ( n = 47), electrocardiography ( n = 46), and echocardiography ( n = 23). Results: Of the 47 patients, 10 had reduced percent forced vital capacity (%FVC), and 4 required non‐invasive positive pressure ventilation. %FVC was significantly correlated with disease duration, and mean %FVC was significantly lower in non‐ambulatory patients, as well as in those aged ≥65 years with normal creatine kinase levels. On electrocardiography, QRS complex duration was prolonged in 19 patients, although no significant association with age, disease duration, or respiratory function was found. Echocardiography indicated no left ventricular dysfunction in any patient. Histopathology of autopsied cases revealed mild cardiomyopathy and moderate diaphragm involvement. Conclusion: Patients with dysferlinopathy may develop severe respiratory failure and latent cardiac dysfunction. Both respiratory and cardiac function should be monitored diligently. Muscle Nerve 53: 394–401, 2016